Digitally Outsourced: The Limitations of Computer-Mediated Transparency. Issue 1 (2nd January 2016) - Koliska, Michael; Chadha, Kalyani
Abstract : The introduction of digital communication technologies has resulted in the emergence of transparency as a journalistic norm. Often termed the "new objectivity, " transparency has been viewed as central to restoring trust in journalism. Not surprisingly, news organizations have claimed they have introduced transparency measures that enable audiences to look behind the curtain of news production. We, however, argue that such efforts primarily involve technological features that are institutionally mandated with little involvement from journalists. That is, transparency in journalism has been digitally outsourced to technology, a development that disconnects journalists from considering and implementing transparency in their work.